DRAMA INTERPRETATION OF THE FAIRY TALE THE SNOW QUEEN BY HANS CHRISTIAN ANDERSEN - Gogolin, Olimpia; Szymik, Eugeniusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The theoretical part introduces the most frequently used drama techniques in early school education of Polish language. The practical part presents drama interpretation of the fairy tale The Snow Queen by Hans Christian Andersen. In the article, drama is introduced as a method that triggers students’ creative expression, which helps them understand the literary text better and ask proper questions.